SOEP 2010 - Preparation of data from the New SOEP consumption module: Editing, imputation, and smoothing - Jan Marcus; Rainer Siegers; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This documentation describes the data preparation of the new consumption module in the German Socio-Economic Panel Study (SOEP) and introduces the content and structure of the generated dataset hconsum. In 2010, the SOEP for the first time included a detailed consumption module in the household questionnaire. This documentation discusses several methodological challenges of the new module and suggests possible remedies. The methodological challenges include inconsistencies between monthly and annual consumption information, missing values, and a high incidence of heaping.
Keywords: C81; D30; E21; 330; SOEP; consumption; heaping; imputation; generalized beta of the second kind